Glutaminase-2 Expression Induces Metabolic Changes and Regulates Pyruvate Dehydrogenase Activity in Glioblastoma Cells - De los Santos-Jiménez, Juan; Campos-Sandoval, José Ángel; Rosales, Tracy; Ko, Bookyung; Alonso, Francisco J.; Márquez-Gómez, Javier; DeBerardinis, Ralph J; Mates-Sánchez, José Manuel (MDPI, 2025)
Glutaminase controls the first step in glutaminolysis, impacting bioenergetics, biosynthesis and oxidative stress. Two isoenzymes exist in humans, GLS and GLS2. GLS is considered prooncogenic and overexpressed in many tumours, while GLS2 may act as prooncogenic or as a tumour suppressor. Glioblastoma cells usually lack GLS2 while they express high GLS. We investigated how GLS2 expression modifies the metabolism of glioblastoma cells, looking for changes that may explain GLS2’s potential tumour suppressive role. We developed LN-229 glioblastoma cells stably expressing GLS2 and performed isotope tracing using U-13C-glutamine and metabolomic quantification to analyze metabolic changes. Treatment with GLS inhibitor CB-839 was also included to concomitantly inhibit endogenous GLS. GLS2 overexpression resulted in extensive metabolic changes, altering the TCA cycle by upregulating part of the cycle but blocking the synthesis of the 6-carbon intermediates from acetyl-CoA. Expression of GLS2 caused downregulation of PDH activity through phosphorylation of S293 of PDHA1. GLS2 also altered nucleotide levels and induced the accumulation of methylated metabolites and S-adenosyl methionine. These changes suggest that GLS2 may be a key regulator linking glutamine and glucose metabolism, also impacting nucleotides and epigenetics. Future research should ascertain the mechanisms involved and the generalizability of these findings in cancer or physiological conditions.
Keywords: Glioma; Cancer; Glioblastoma; Glutamine; Glutaminase; Glutaminase-2; Metabolomics; Pyruvate dehydrogenase